2016
DOI: 10.1128/mcb.00600-15
|View full text |Cite
|
Sign up to set email alerts
|

Chordin-Like 1 Suppresses Bone Morphogenetic Protein 4-Induced Breast Cancer Cell Migration and Invasion

Abstract: ShcA is an important mediator of ErbB2-and transforming growth factor ␤ (TGF-␤)-induced breast cancer cell migration, invasion, and metastasis. We show that in the context of reduced ShcA levels, the bone morphogenetic protein (BMP) antagonist chordin-like 1 (Chrdl1) is upregulated in numerous breast cancer cells following TGF-␤ stimulation. BMPs have emerged as important modulators of breast cancer aggressiveness, and we have investigated the ability of Chrdl1 to block BMP-induced increases in breast cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 64 publications
0
60
0
Order By: Relevance
“…2A and SI Appendix, Fig. S3A) (40). It is unclear what role CHRDL1 may play in the progressing stage of PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…2A and SI Appendix, Fig. S3A) (40). It is unclear what role CHRDL1 may play in the progressing stage of PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…CHRDL1 is a secreted protein and antagonist of bone morphogenetic protein (BMP) that antagonizes BMP-4 activity and induces differentiation of spinal cord-derived [29]. Since no research has proved that CHRDL1 is related to thyroid cancer, more research is needed to verify the association between CHRDL1 and thyroid cancer and evaluate CHRDL1 as a target for thyroid cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…They are multifunctional growth factors that belong to the superfamily of transforming growth factor-β (TGF-β) (20). Cyr-Depauw et al (21) demonstrated that under decreased ShcA signaling conditions, CHRDL1 expression is upregulated in a large amount of breast cancer cells following TGF-stimulation. The authors also observed that CHRDL1 plays a role as an inhibitor of BMP4-induced migration and invasion by the way of in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%